Characterization of Alginate-Cellulose-Kaolin Composites for Slow-Release Urea Fertilizer - Sunardi, Sunardi; Faramitha, Gusti Nia; Santoso, Uripto Trisno (Indonesian Journal of Chemical Research, 2021)
Research on the effect of cellulose and kaolin addition to alginate-cellulose-kaolin composites' characteristics as a slow-release agent of urea fertilizer has been done. The technique used in composites' preparation is an extrusion technique using 2% CaCl2 solution as a cross-linker. The compositions of alginate-cellulose-kaolin were varied to determine their effect on composites' characteristics such as diameter, color, swelling ratio, entrapment efficiency, and release of urea. The results showed that the diameter of beads in wet condition produced ranges from 2.98 to 3.54 mm, whereas the diameter of dry beads ranges from 1.22 to 1.92 mm. The addition of cellulose and kaolin affected the color of the beads produced based on CIE Lab analysis. The value of the swelling ratio decreased with the addition of cellulose and kaolin. The entrapment efficiency of urea in beads obtained ranged from 37.25 to 45.06%. The release of urea in aqueous media showed that cellulose and kaolin's addition into the alginate affected the amount of released urea.